Proteinases of Pseudomonas aeruginosa evoke mucin release by tracheal epithelium. - Klinger, J D (1984)
We have determined the potential of exoproducts from pathogenic bacteria to stimulate the release of high molecular weight mucins from goblet cells of airway epithelium in a rabbit tracheal explant system. Culture supernatants from proteolytic strains of Pseudomonas aeruginosa and Serratia marcescens, but not supernatants from a number of non-proteolytic strains, released mucins from goblet cells. Highly purified elastase and alkaline proteinase from P. aeruginosa stimulated goblet cell mucin release in a dose-dependent fashion. Lipopolysaccharide, exotoxin A, and alginate of P. aeruginosa did not possess mucin release properties. Proteolytic activity was required for mucin release by P. aeruginosa elastase, but such release in goblet cells was not mediated by cyclic AMP. Morphologic studies suggested rapid release of mucins from goblet cells was response to elastase by a process resembling apocrine secretion. Several nonbacterial proteinases mimicked the effect of Pseudomonas proteases. These studies provide support for the hypothesis that bacterial and other play a role in the pathogenesis of mucus hypersecretion in acute and chronic lung infections.